The East Greenland Spill Jet as an important component of the Atlantic Meridional Overturning Circulation - von Appen, Wilken-Jon; Koszalka, Inga M.; Pickart, Robert S.; Haine, Thomas W. N.; Mastropole, Dana M.; Magaldi, Marcello G.; Valdimarsson, Héðinn; Girton, James B.; Jochumsen, Kerstin; Krahmann, Gerd (Deep Sea Research Part I: Oceanographic Research Papers, 2014)
Author Posting. © The Author(s), 2014. This is the author's version of the work. It is posted here by permission of Elsevier for personal use, not for redistribution. The definitive version was published in Deep Sea Research Part I: Oceanographic Research Papers 92 (2014): 75-84, doi:10.1016/j.dsr.2014.06.002. The recently discovered East Greenland Spill Jet is a bottom-intensified current on the upper continental slope south of Denmark Strait, transporting intermediate density water equatorward. Until now the Spill Jet has only been observed with limited summertime measurements from ships. Here we present the first year-round mooring observations demonstrating that the current is a ubiquitous feature with a volume transport similar to the well-known plume of Denmark Strait overflow water farther downslope. Using reverse particle tracking in a high-resolution numerical model, we investigate the upstream sources feeding the Spill Jet. Three main pathways are identified: particles flowing directly into the Spill Jet from the Denmark Strait sill; particles progressing southward on the East Greenland shelf that subsequently spill over the shelfbreak into the current; and ambient water from the Irminger Sea that gets entrained into the flow. The two Spill Jet pathways emanating from Denmark Strait are newly resolved, and long-term hydrographic data from the strait verifies that dense water is present far onto the Greenland shelf. Additional measurements near the southern tip of Greenland suggest that the Spill Jet ultimately merges with the deep portion of the shelfbreak current, originally thought to be a lateral circulation associated with the sub-polar gyre. Our study thus reveals a previously unrecognized significant component of the Atlantic Meridional Overturning Circulation that needs to be considered to understand fully the ocean’s role in climate. Support for this study was provided by the U.S. National Science Foundation (OCE-0726640, OCI-1088849, OCI-0904338), the German Federal Ministry of Education ...